Survival after Surgery in Patients with Spontaneous Intracerebral Hemorrhage by Degree of Midline Shift from CT Scan and ICU Importance after the Surgery at Pranangklao Hospital Nonthaburi Province - ปิยผดุงกิจ, สุริยะ (Journal of Health Science of Thailand, 2020)
The objective of this study was to evaluate the use of midline shift for estimating results after surgery, and role of intensive care unit (ICU) on the patients’survival. It was conducted as a retrospective study of 157 patients after the surgery for spontaneous intracerebral hemorrhage who admitted to Pranangklao Hospital between October 2015 and September 2018. All patients had spontaneous supratentorail intracerebral hemorrhage. Patients with bleeding tumor, ruptured aneurysm, ruptured AVM, infratentorial hemorrhage and traumatic intracerebral hemorrhage (from accident, assaulted, falling or other causes) were excluded. The patients were divided into 3 groups: group of midline shift <8 mm., >8–10 mm. and >10mm. Their survival, ventilator using time and recovery status at discharge time were compared. Each group had been admitted in an ICU and a non-ICU randomly depending on ICU-bed status at admission time. The treatment outcomes between patients in ICU and non-ICU were also compared after the surgery. Almost all patients (147/157=93.6%) were intubated. Survival of patients with midline shift <8 mm. (n=59) was 66.1%, >8-10 mm. (n=39) was 43.6% and >10 mm. (n=59) was 33.9% (p<0.05). Patients with midline shift <8 mm. had significantly better recovery with the GOS 3 of 44.1%, compared to 33.3% in the group with the shift of >8-10 mm., and 18.6% in the >10 mm. group (p<0.05). Patients in ICU showed statistically significant better survival than the non-ICU. The survival rate for patients with midline shift <8 mm. was 90.0% in ICU sub-group and 41.4% in the non-ICU (p<0.05). Those with midline shift >8 –10 mm. the survival rate in ICU was 83.3% and in non-ICU - 9.5% (p<0.05 ). And those with midline shift >10 mm. the survival in ICU was 52.0%, and in non-ICU - 20.6% (p<0.05). The study demonstrated that midline shift from CT scan was a factor affecting survival after the surgery for spontaneous intracerebral hemorrhage. Patients with midline shift <8 mm. had more rapid weaning of ventilator with better survival and recovery. Thus, the midline shift from CT scan can be used to predict the treatment results after surgery. In addition, ICU is important for the better survival after the surgery for spontaneous intracerebral hemorrhage all 3 groups. In conclusion, increasing the number of ICU beds to meet the patients’ demand or selecting patients according to after surgery results by using midline shift especially midline shift <8 mm. for ICU admission and proper management in case of limited ICU beds would increase patients’survival.